Responsible use of ChatGPT in ESL: teachers’ perspective - Chugai Oksana; Havrylenko Kateryna (Науковий Вісник Південноукраїнського Національного Педагогічного Університету імені К. Д. Ушинського)
ChatGPT has become an essential educational tool, highlighting the importance of understanding its impact and potential in the classroom. While many studies explore AI applications, the ethical issues surrounding ChatGPT’s use in language teaching have received less attention. This article addresses this gap by investigating ESL teachers’ perspectives on the responsible use of ChatGPT. The study involved 33 English as a Second Language (ESL) teachers from universities and schools in Ukraine. Quantitative data was analyzed using the median (Mdn) and Inter-Quartile Range (IQR) on a five-point Likert scale, while qualitative data was drawn from written responses. In terms of demographics, most respondents were aged 35 to 54 with more than half over 21 years of teaching experience. Regarding their attitudes toward ChatGPT’s impact, over half viewed it as a valuable tool for enhancing ESL students’ language skills, and 55% supported its use for generating ideas and content. On ethical considerations, most teachers agreed that students should be aware of the ethics of using ChatGPT. Two-thirds of respondents felt students should rely more on their efforts. Half were unsure if students could differentiate their work from ChatGPT-generated content. Regarding guidelines, 82% of teachers believed students need training on ethical use, and 80% thought students should face penalties for misuse. A majority (85%) agreed students understand the consequences of improper use and supported training ESL teachers to guide students on ChatGPT’s use. Two-thirds believed discussions could help reduce unethical use. Respondents showed the highest level of agreement on the need for ethical ChatGPT’s use and teacher training (IQR = 0), the strongest agreement was on the necessity of ethical awareness (Mdn = 5). The findings of this study can inform policy decisions on integrating AI in foreign language teaching and support the development of teacher training programs focused on the ethical use of AI tools.